The impact of pectoralis major fascia preservation on postoperative quality of life and shoulder function in endoscopic thyroidectomy via axillary approach - Xu, Hang; Li, Sihan; Wang, Xulin; Zhang, Benlong; Wang, Yaqi; Lu, Chang; Deng, Cheng; Lei, Shangtong (Frontiers in Endocrinology, 2025)
BackgroundThe impact of pectoralis major fascia (PMF) preservation during endoscopic thyroidectomy (ET) via axillary approach on postoperative recovery remains poorly understood. This study aimed to compare the quality of life (QoL) and shoulder function between patients with and without PMF preservation intraoperatively.MethodsA total of 77 patients were enrolled, including 39 cases with the PMF preservation (Group A) and 38 cases without (Group B). Postoperatively QoL and shoulder joint function were assessed at 1month, 3 months, and 6 months using Thyroid Cancer-Specific Quality of Life (THYCA-QoL) questionnaire and American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) questionnaire, respectively.ResultsThe median follow-up time was 7.55 ± 1.36 months across all cases. Intraoperatively, Group A exhibited significantly lower total drainage volume than Group B (p <0.001). During postoperative follow-up, while THYCA-QoL scores were comparable at 1 and 6 months, Group A demonstrated superior neuromuscular (p = 0.03), sympathetic (p = 0.01), and sensory (p = 0.01) recovery at 6 months. ASES scores revealed no differences at 1 month, however, by 3 months, Group A achieved higher total scores (p = 0.02). At 6 months, Group A outperformed Group B in total ASES score (p < 0.001), pain (p = 0.04), and function (p < 0.001).ConclusionPreserving the PMF during ET via an axillary approach can improve QoL, reduce bleeding, enhance long-term sensory and shoulder functional recovery, suggesting that the protection of PMF might have a positive impact on the postoperative patient recovery.